Some Existence, Uniqueness, and Stability Results for a Class of ϑ-Fractional Stochastic Integral Equations - Fahad Alsharari; Raouf Fakhfakh; Omar Kahouli; Abdellatif Ben Makhlouf (Fractal and Fractional)
This paper focuses on the existence and uniqueness of solutions for <semantics>ϑ</semantics>-fractional stochastic integral equations (<semantics>ϑ</semantics>-FSIEs) using the Banach fixed point theorem (BFPT). We explore the Ulam–Hyers stability (UHS) of <semantics>ϑ</semantics>-FSIEs through traditional methods of stochastic calculus and the BFPT. Moreover, the continuous dependence of solutions on initial conditions is proven. Additionally, we provide three examples to demonstrate our findings.